Waiting for a download: The effect of congruency between anthropomorphic cues and shopping motivation on consumer patience. Issue 12 (4th August 2021) - Chen, Siyun; Wei, Haiying; Ran, Yaxuan; Li, Qing; Meng, Lu
Abstract: Consumers tend to be impatient during an online wait (e.g., waiting for webpages to download), which may decrease their satisfaction with online retailers. The current research addresses this important issue by identifying a simple and viable strategy to boost consumer patience: the presence of anthropomorphic cues on the download interface. In particular, we postulate a matching effect between anthropomorphic cues and shopping motivation on consumer patience, such that hedonic (vs. utilitarian) consumption benefits from exciting (vs. sincere) anthropomorphism, whereas utilitarian (vs. hedonic) consumption benefits from sincere (vs. exciting) anthropomorphism (Study 1). Notably, these effects are driven by a match between anthropomorphic cues and shopping motivation that creates perceptions of fluency, and the ensuing enjoyment experience yields enhanced patience (Study 2). In addition to having substantive theoretical implications for the anthropomorphism, patience, and persuasion literature, our findings offer novel insights regarding ways for marketers to effectively manage online wait.